Asuhan Kebidanan Komprehensif: Pada Ny “P”Dengan Kekurangan Energi Kronik (Kek) di Praktek Mandiri Bidan Dewi Ciselia - Ciselia, Dewi; Ariyani, Yulinda; Sari, Yona (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Chronic Energy Deficiency (KEK) is a state of malnutrition, Pathological due to a relative or absolute deficiency or excess of one or more nutrients, and the measurement results of the lila are less than 23.5 cm.  According to data from the World Health Organization (WHO) in 2017, the maternal mortality rate throughout the world is estimated at 210/100,000 live births and the neonatal mortality rate has decreased by 38%, namely 36/1000 births. Of all maternal deaths, this is severe bleeding, generally bleeding after childbirth, postpartum infections. , high blood pressure during pregnancy (preeclampsia and eclampsia). The research study method was carried out using a continuous care approach (Countuinity of care) or what is called Comprehensive Midwifery Care with Midwifery Care standards. The target in this case study is Mrs. P, 36 weeks pregnant with her first child, who is willing to sign an informed consent form. The Midwifery Care research study was carried out at the Independent Practice of Midwife Dewi Ciselia in 2024. The time used was 22 July 2024 to 30 July 2024. After being given comprehensive Midwifery Care during the postpartum period, there were 2 repeat visits, no complications or complications were found and in accordance with midwifery service standards, newborns have 2 repeat visits, use birth control injection contraception for 3 months and do not difficulties or complications are found and in accordance with obstetric service standards.